Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Boyolali - Naia Rose Milano; Dianing Widya Kusumastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research seeks to examine the influence of taxpayer knowledge, taxpayer awareness, and tax sanctions on the compliance of motor vehicle taxpayers in Boyolali Regency. Motor vehicle tax constitutes a significant component of regional original revenue; however, the level of revenue realization has not yet fully met the established targets, indicating the presence of compliance-related challenges. The study adopts a quantitative explanatory design. Primary data were obtained by distributing questionnaires to 100 motor vehicle taxpayers registered at the Boyolali Samsat Office, with respondents selected through accidental sampling based on the Slovin formula. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, following preliminary tests of validity, reliability, and classical assumptions. The findings demonstrate that taxpayer knowledge and taxpayer awareness exert a positive and statistically significant effect on motor vehicle taxpayer compliance. In addition, tax sanctions are also shown to have a positive and significant impact and represent the most dominant factor influencing compliance. These results are consistent with Attribution Theory and the Theory of Planned Behavior, which highlight the importance of both internal and external determinants in shaping taxpayer compliance behavior. This study is expected to provide empirical support for research on regional tax compliance and offer practical insights for local governments in developing strategies to improve motor vehicle tax compliance.